The effects of immersive multimedia learning with peer support on speaking skill among male and female students - Asnawi Asnawi (Universitas Syiah Kuala, 2015)
This study investigated the effects of immersive multimedia language learning technique on performance in English in terms of oral production skills in reading and speaking that involved six measures, namely, pausing, phrasing, stress, intonation, rate, and integration without the mediation of the first language of the students amongst both males and females. A quasi-experimental design was employed for the study. Eighty first-year university students enrolled in English as a Foreign Language (EFL) course were selected for this study and the teaching treatment was followed for eight sessions with one session per week. Data were analysed using one-way ANOVA. The findings showed that following the immersive multimedia learning, male students in the immersive multimedia group with peer support performed significantly better in four of the six measures of reading skills, namely, phrasing, stress, intonation, and integration as compared to their counterparts in the non-peer supported groups and there were no significant differences for pausing and rate. On the other hand, female students in the immersive multimedia learning with peer support group performed significantly better in all six measures of oral production for reading and speaking than their counterparts in the groups without peer support.  These findings showed that the immersive multimedia technique with peer support reduced the use of code-switching strategies by the students and enabled them to develop oral production skills in English approaching the patterns of native speakers especially amongst the female students.